Culturally Sensitive using Technology: Exploring the Crossroads of Technology and the Recognition of Children’s Cultural Rights - Thomassen Andersen, Synnøve (NAVEIÑ REET: Nordic Journal of Law and Social Research, 2025)
This research presents a research agenda focused on examining the influence of teachers’ attitudes and cultural sensitivity on the preservation of children’s cultural rights. To effectively analyze this area, the utilization of technology is proposed as it offers an efficient and comprehensive means to explore this topic. To gain deeper insights into the thoughts and experiences of teachers, qualitative methods and individual interviews are used. This approach allows for a thorough understanding of the subject matter, facilitating a nuanced analysis. The UN Convention on the Rights of the Child is suggested as an analytical framework to evaluate the findings against internationally recognized principles. This framework enables a more comprehensive and comparable analysis. The primary objective of this research is to identify the strengths and challenges in teachers’ cultural sensitivity and to contribute to the enhancement of children’s rights to their own culture. Furthermore, this study acknowledges the advantages and obstacles associated with the use of technology in promoting cultural visibility among children. Consequently, there is a need for further research in this field.